2023
DOI: 10.3758/s13414-023-02707-3
|View full text |Cite
|
Sign up to set email alerts
|

Problematic smartphone usage, objective smartphone engagement, and executive functions: A latent variable analysis

Abstract: The negative consequences of smartphone usage have seen frequent discourse in popular media. While existing studies seek to resolve these debates in relation to executive functions, findings are still mixed, partly due to the lack of conceptual clarity, the use of self-reported measures, and task impurity. Addressing these limitations, the current multi-session study utilizes latent variable approaches to examine various smartphone usage, including objectively measured data-logged screen time and screen-checki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…In relation to RQ3, we found differences in the PSU and bedtime procrastination variables in young adults (18-25 years) versus adults and middle-aged adults (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60), but no differences in sleep quality. The differences in PSU are consistent with the literature [138], and are possibly due to the fact that younger people spend more hours on their smartphone (both variables correlate significantly, as can be seen in Table 3) and that younger generations have grown up with this technology [139].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In relation to RQ3, we found differences in the PSU and bedtime procrastination variables in young adults (18-25 years) versus adults and middle-aged adults (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60), but no differences in sleep quality. The differences in PSU are consistent with the literature [138], and are possibly due to the fact that younger people spend more hours on their smartphone (both variables correlate significantly, as can be seen in Table 3) and that younger generations have grown up with this technology [139].…”
Section: Discussionmentioning
confidence: 84%
“…Several negative consequences of PSU have been found, such as low productivity [50], poor academic performance [51,52], general procrastination [53], academic procrastination [54], low self-esteem [55], increased alcohol consumption [52], anxiety and depression [56][57][58], executive function deficiencies [59,60] and sleep problems [61][62][63][64][65]. Melatonin is a hormone secreted by the pineal gland and regulated by sleep-inducing light/dark cycles.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that the adverse effects of smartphone use on general attention capacity are not remarkable in the general population [ 71 ]. A recent study also reported no significant impairment in overall cognitive function as assessed through behavioral tasks in problematic smartphone use [ 72 ]. Consistent with these previous studies, our current findings suggest that impairments in general attentional function are not evident for problematic smartphone use.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout our meta-analysis, we also observed that almost all experimental studies on mere presence of smartphone assessed executive functions using scores from singular tasks (e.g., OSPAN, Stroop task). This approach to operationalize cognitive functioning is problematic as studies have consistently reported low intercorrelations among tasks measuring executive functions, driven by the involvement of nonexecutive abilities in most executive function tasks (Friedman & Miyake, 2004;Hartanto, Chua et al, 2023;Miyake et al, 2000). For example, performance on the Stroop task is not purely driven by the ability to resist the distraction from the word name but also involves phonological recoding, associative facilitation, visual recognition, and color discrimination abilities (MacLeod, 1991;Mahon et al, 2012;Naish, 1980).…”
Section: Discussionmentioning
confidence: 99%